Aplicación del convenio de la haya sobre los aspectos civiles de la sustracción internacional de menores en el perú - Chávez Barbarán, Verónica Haydeé (2013)
In many processes on possession, custody and visitation rights, where involved parties of different nationalities, the judges of the State who knows the subject, are usually granted the custody and care of the minor to a national subject of such a State, and give a mere right to visit the other subject, who mostly turns out to be a citizen of a foreign country. These cases occur mostly after a divorce or in the course of the processing of the same. A large part of the cases of international child abduction (Legal Kidnapping) occurs when the subject has the right to visit, taking advantage of one of these periods, moved to the lower abroad. In the country requesting the custody and care of the minor, illegal for the country that has come out, trying to "legalize" his situation in his country. The number of cases of international legal abduction of minors is, unfortunately, very high around the world since the seventies, and our country is no stranger to this problem, where in the past have increased these cases. The first issue of legal Kidnapping in Spain - a country that develops so legislatively this item - was the failed by the STS April 8 1975, Bornes vs. Fuentes. Lately these cases have achieved notoriety for his journalistic politicization: case Eneko, son of a Spanish citizen, which claimed the custody of the same, and German citizen converted to islam, who was kidnapped by this and moved to Yemen; so also by the sensitivity which cause, as is the case of Eliancito, the "child oarsman". Therefore, our interest in performing this research, seeking to possible solutions to this problem and disseminate the most important aspects of international child abduction